Análise do custo de oportunidade das suspensões cirúrgicas sob o olhar da inteligência do negócio - Costa Junior, Edelzio Alves (2022)
An economic-financial perspective study innovates by bringing opportunity cost analyzes to the discussions on surgical suspensions from the perspective of a business intelligence environment. Objective. Analyze the opportunity cost of surgical suspensions from the point of view of business intelligence. Materials and methods. Exploratory-descriptive study with a hypothetical-deductive longitudinal approach that aims to observe the phenomena that occurred at a given time through a representative sample of 6 years, delimited by elective suspended outpatient and hospital surgeries, extracted from the Surgery Management System – SIGEC. The data includes inputs, maintenance services and condominium expenses such as water, energy, and telephony, fed through the SUS Calculation and Cost Management System - APURASUS, which were extracted from the Warehouse Management System - GENUS and the Federal Government's Integrated Financial Administration System – SIAFI. Health products, medicines, laboratory materials and orthoses, prostheses, and special materials, which are directly related to the act of performing the surgery, were excluded. Results and discussions. Statistical inferences made with age, sex, size, and specialty predictors showed that age is not significant for determining the reason for surgical suspension and opportunity cost. It is also evidenced, in the analysis of the graphs and reports presented in the management panel, developed through the business intelligence tool, that the highest opportunity cost occurred in the year 2018, in surgeries such as laparoscopic cholecystectomy, Block, total thyroidectomy and pancreatoduodenectomy; in the reasons for surgical suspension, rescheduling and unfavorable clinical conditions, being more than 90% related to operational costs; and these avoidable costs corresponded to almost 80%. Conclusions. The business intelligence environment proved to be functional in supporting the analysis and trends of the opportunity cost of suspended surgeries.